THE ACTIVITY OF INTERNAL AFFAIRS IN THE KHOREZM REGION IN THE 30S OF THE 20TH CENTURY - Yulduz Ravshanbek Qizi, Khamdamova (PT. Antis International Publisher, 2024)
Objective: This study investigates the structural reforms in Uzbekistan’s internal affairs system during the 1930s, with a focus on the Khorezm region under Soviet governance, aiming to understand their impact on law enforcement efficiency and social stability. Method: A historical analysis was conducted using archival documents, periodicals, and academic sources to examine the organizational changes and policy implementations within internal affairs bodies. Results: The findings reveal significant expansions in police responsibilities, restructured organizational frameworks, and strategic policies that enhanced public order and personal security. These reforms not only improved crime prevention and law enforcement efficiency but also served as instruments for political control, reinforcing the Soviet state's authority. Novelty: This research offers a comprehensive analysis of how Soviet-era reforms in internal affairs contributed to the foundation of modern law enforcement in Uzbekistan, highlighting their dual role in societal governance and state control—an area that has been underexplored in existing literature.